Decoding Factors Influencing Knowledge Sharing Among Indonesian Scholars - Sarah Fadilla; Adisthy Shabrina Nurqamarani; Ari Juliana (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2024)
This study examines the determinant factors of knowledge-sharing intention and behaviour among academics in Indonesia. Academics need to compete and excel in global competition amidst obstacles such as qualification, competency, and working culture. The study integrated the Theory of Planned Behavior, Social Capital Theory, and perceived cost. A questionnaire was distributed online to academics, and 239 respondents were obtained. Data analysis was undertaken by using SEM-PLS. The result found that all the variables examined were determined to be significant, except commitment, extrinsic reward, and facilitating condition. The importance of social networks, trust, self-efficacy, management support, social media use, and perceived cost among academics. The result can help management better understand how to create a knowledge-sharing environment in the institution, significantly higher education institutions with open and distance learning systems.